Model Epidemi Suspected Exposed Infected Recovered (SEIR) Pada Penyebaran COVID-19 Orde-Fraksional - Nisa, Khoirotun; Rahman, Hairur; Kusumastuti, Ari (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
This article discusses the solution to the fractional order SEIR equation with the help of the Homotopy Perturbation Method (HPM). This mathematical model is the SEIR model of the spread of COVID-19 cases in Indonesia. In general, the nonlinear Ordinary Differential Equation System (ODES) solution is quite difficult to solve analytically, so this research will transform the nonlinear ODES into a Fractional Differential Equation System (FDES). The method used in completing this research is the HPM method. The solution for the fractional order by the HPM method is obtained by the following steps: 1). Multiply each SEIR equation against the embedding parameter and equate each coefficient in the assumed infinite series to find the solution, 2). Simulate numerical solutions and perform graph interpretation. The numerical simulation shows that the susceptible human population, the infected human population without symptoms, the recovered human population has increased, in contrast to the infected human population with decreased symptoms. The HPM method in its numerical solution shows a fairly small comparison to the nonlinear ODES solution.